2019
DOI: 10.3390/microorganisms7100455
|View full text |Cite
|
Sign up to set email alerts
|

Global Transcriptional Response of Three Highly Acid-Tolerant Field Strains of Listeria monocytogenes to HCl Stress

Abstract: Tolerance to acid is of dual importance for the food-borne pathogen Listeria monocytogenes: acids are used as a preservative, and gastric acid is one of the first defenses within the host. There are considerable differences in the acid tolerance of strains. Here we present the transcriptomic response of acid-tolerant field strains of L. monocytogenes to HCl at pH 3.0. RNAseq revealed significant differential expression of genes involved in phosphotransferase systems, oxidative phosphorylation, cell morphology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 92 publications
1
8
0
Order By: Relevance
“…In E. coli, phosphotransacetylase Pta and the acetate kinase AckA have been shown to reversibly convert acetate to acetyl CoA [32,41]. This is also consistent with the observed up-regulation of the transcripts qoxA, qoxC and qoxA, which are upregulated in L. monocytogenes in response to acid stress [42]. However, two transcripts, atpD and atpC, coding for the β and ε subunits of the F 1 F 0 -type ATP synthetase are significantly up-regulated at the 44h timepoint relative to the aerobic (8h) timepoint.…”
Section: Temporal Dynamics Of P Thermoglucosidasius Dsm 6285 Transcrsupporting
confidence: 81%
“…In E. coli, phosphotransacetylase Pta and the acetate kinase AckA have been shown to reversibly convert acetate to acetyl CoA [32,41]. This is also consistent with the observed up-regulation of the transcripts qoxA, qoxC and qoxA, which are upregulated in L. monocytogenes in response to acid stress [42]. However, two transcripts, atpD and atpC, coding for the β and ε subunits of the F 1 F 0 -type ATP synthetase are significantly up-regulated at the 44h timepoint relative to the aerobic (8h) timepoint.…”
Section: Temporal Dynamics Of P Thermoglucosidasius Dsm 6285 Transcrsupporting
confidence: 81%
“…Multiple studies have demonstrated that lmo2230 is a member of the σ B regulon (Raengpradub et al, 2008;Oliver et al, 2009;Toledo-Arana et al, 2009;Utratna et al, 2011). These studies also showed that lmo2230 is upregulated during early stationary phase (Raengpradub et al, 2008;Oliver et al, 2009), within the murine intestinal lumen (Toledo-Arana et al, 2009) and in response to osmotic and acid stress (Raengpradub et al, 2008;Utratna et al, 2011;Horlbog et al, 2019). Heat and cold stress have also been shown to induce lmo2230 expression (van der Veen et al, 2007;Hingston et al, 2017a), and lmo2230 is also upregulated after chlorine dioxide exposure (Pleitner et al, 2014).…”
Section: σ B Genesmentioning
confidence: 95%
“…In addition to differences in experimental conditions, the differences in upregulation of lmo2230 could be explained by different timepoints, different L. monocytogenes strains, and/or the usage of a microarray compared to RNA sequencing. Although upregulation of lmo2230 in response to stress has been observed in numerous studies (van der Veen et al, 2007;Raengpradub et al, 2008;Oliver et al, 2009;Toledo-Arana et al, 2009;Utratna et al, 2011;Pleitner et al, 2014;Hingston et al, 2017a;Horlbog et al, 2019), its function in L. monocytogenes remains uncharacterized. The weak amino acid identity of Lmo2230 to the arsenate reductase ArsC from B. subtilis might suggest a possible role in heavy metal detoxification.…”
Section: σ B Genesmentioning
confidence: 99%
“…However, these stress responses entail an extensive cell reprogramming with pleiotropic effects, which are still poorly understood. For example, recent transcriptomic analyses involving distinct L. monocytogenes strains subjected to acidic conditions (pH = 3.0) showed enhanced expression of genes belonging to both GAD and ADI systems, along with hundreds of differentially expressed genes with no obvious involvement in acid tolerance [ 141 , 142 ]. This is also true of other stress responses, such as those triggered by low temperature [ 101 ], high osmolality [ 143 ], QACs [ 144 ], or bile salts [ 140 ].…”
Section: Listeria Responds To Environmental Stressmentioning
confidence: 99%